Return to nature : the new science of how natural landscapes restore us - Loewe, Emma (HarperOne, 2022)
"For centuries, humankind was connected to nature. Yet we've evolved to feel safer inside on our devices, despite the fact that most of us are our most calm, creative, and captivated outdoors. In response, writer and environmentalist Emma Loewe blends new research and ancient spiritual knowledge on the healing properties of landscape to prove why we need to return to nature for the sake of our health--and the planet's." -- Back cover.